2018
DOI: 10.5812/hepatmon.64380
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease and Liver Fibrosis in Bariatric Patients: Tehran Obesity Treatment Study (TOTS)

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) has become a leading cause of chronic liver disease worldwide. We aimed to study this condition and liver fibrosis in bariatric patients at baseline using ultrasound, NAFLD fibrosis score (NFS), and fibrosis index-4 (FIB-4). Methods: Adult patients with morbid obesity without other possible causes of liver pathology were evaluated. Liver biopsy was performed in a subset of patients. Diagnostic accuracy of tests was assessed using area under the receiver ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…LF prevalence was also 3.6% in a study in Europe and 2.9% in a study in South Korea [7]. Moreover, a study in Iran showed that the prevalence of advanced LF among obese people was 10.4% [8].…”
Section: Introductionmentioning
confidence: 87%
“…LF prevalence was also 3.6% in a study in Europe and 2.9% in a study in South Korea [7]. Moreover, a study in Iran showed that the prevalence of advanced LF among obese people was 10.4% [8].…”
Section: Introductionmentioning
confidence: 87%
“…Non-alcoholic fatty liver (NAFLD) occurs when extra fat accumulates in hepatocyte leading to elevated liver enzymes, steatohepatitis, liver fibrosis, cirrhosis and liver cancer [5]. It is associated with metabolic syndrome, dyslipidemias and insulin resistance [6].…”
mentioning
confidence: 99%